Analysis in silico and prediction of mode of action of potential inhibitors of H. pylori urease extracted from medicinal plants - Khadroune, Fatima Zahra Soraya; Gueddouda, Bouchra Amina; Zakhrouf, Zohra, Directeur de thèse; Boukerouis, Djoudi, Directeur de thèse (Laghouat : Université Amar Telidji - Département de biologie, 2024)
Helicobacter pylori infection is a major cause of gastrointestinal diseases like gastritis, peptic ulcers, and gastric cancer. The bacterium survives in the stomach’s acidic environment due to its urease enzyme, which neutralizes stomach acid. Our research explores traditional medicinal plants for potential urease inhibitors. We selected five plants: Salvia officinalis, Nigella sativa, Eucalyptus globulus, Zingiber officinale, and Trigonella foenum-graecum. We conducted molecular docking studies to examine the interaction of natural compounds from these plants with the urease enzyme. Compounds like quercetin, gallic acid, and vanillic acid showed significant urease inhibitory activity. Quercetin, in particular, demonstrated strong non-competitive inhibition by binding to the enzyme’s flap region, preventing its active conformation. Gallic acid and vanillic acid also formed stable interactions with key residues in the enzyme’s active site. Further in silico analysis revealed that these compounds have favorable pharmacokinetic properties and low toxicity, making them promising therapeutic candidates. Our findings suggest that these natural inhibitors could provide viable alternatives to current treatments, addressing antibiotic resistance and offering safer therapeutic options.